2015
DOI: 10.2337/db15-er04
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Both Rab-GTPase–Activating Proteins TBC14KO and TBC1D4 in Mice Eliminates Insulin- and AICAR-Stimulated Glucose Transport. Diabetes 2015;64:746–759

Abstract: During production, two errors were introduced to the article listed above. The first is in the title, which should read "Deletion of Both Rab-GTPase-Activating Proteins TBC1D1 and TBC1D4 in Mice Eliminates Insulin-and AICAR-Stimulated Glucose Transport." The second is in the first sentence of the abstract, which should read "The Rab-GTPase-activating proteins TBC1D1 and TBC1D4 (AS160) were previously shown to regulate GLUT4 translocation in response to activation of AKT and AMPdependent kinase." The editors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…C–G). InsR–Akt pathway regulates TBC1D4 to stimulate the translocation of GLUT4 to plasma membrane . Together, these data support the notion that WNK1 may contribute to GLUT4 translocation by the stimulation of InsR signaling cascades.…”
Section: Resultssupporting
confidence: 78%
“…C–G). InsR–Akt pathway regulates TBC1D4 to stimulate the translocation of GLUT4 to plasma membrane . Together, these data support the notion that WNK1 may contribute to GLUT4 translocation by the stimulation of InsR signaling cascades.…”
Section: Resultssupporting
confidence: 78%
“…] insulin plasma levels (Szekeres et al 2012), subsequent reports have not replicated this finding. Specifically, although not statistically different, the single KO of TBC1D1 appears to display the lowest insulin value during a GTT compared with WT, AS160 KO, or combined AS160-TBC1D1 double KO mice (Szekeres et al 2012;Dokas et al 2013;Chadt et al 2015;Hargett et al 2016). Moreover, it has recently been reported that combined AS160-TBC1D1 ablation decreases serum insulin concentrations during a GTT, whereas AS160 independent KO does not.…”
Section: Tbc1d1 Is Required To Maintain Pancreatic ␤-Cell Massmentioning
confidence: 81%
“…In the present study we examined a TBC1D1-deficient rat model to address the role of TBC1D1 in glucose homeostasis in vivo. While current murine models of TBC1D1 deficiency report a ϳ50% reduction in skeletal muscle GLUT4 content (Szekeres et al 2012;Dokas et al 2013;Chadt et al 2015;Hargett et al 2016), this finding confounds insulin sensitivity results in mice. In the present study, we demonstrated that the rat model of TBC1D1 deficiency has normal GLUT4 protein expression, allowing for a discriminative investigation into the role of TBC1D1 in glucose homeostasis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Purified GST‐Rab fusion proteins (0.6 μ m ) were loaded with 0.1 μ m [γ‐ 32 P]GTP (Hartmann Analytic, Braunschweig, Germany) in 20 m m Tris/HCl, 5 m m MgCl 2 , 1 m m DTT, 0.02% (w/v) BSA, pH 8.0 as described . After adding 0.6 μ m purified GST‐GAP domains, aliquots were removed at time 0 and 16 min, and radioactive [ 32 P]phosphate was separated from nucleotides by filtration through activated charcoal . Radioactivity in the filtrate was determined by scintillation counting.…”
Section: Methodsmentioning
confidence: 99%